Data-Driven Problem-Solving in International Business Communication - Zielonka, Alexander (Peter Lang GmbH, 2017)
This study challenges the traditional approach of focusing on English as a foreign language learning in international business settings. The primary objective in such settings is to successfully create a linguistically correct document. Rather than relying on accumulated incomplete individual language knowledge, an alternative approach is to «solve a written language problem» by employing online tools to search for certain unknown technical terms. The author of this study advocates that the use of bilingual text search engines as a more viable problem-solving tool than traditional online dictionaries. Therefore, he examines how well participants are able to select correct verb-object expression using either an online dictionary or a bilingual text search engine.
10.3726/b11200
Keywords: Hochschulschrift; Unternehmen; Kommunikation; Englisch; Internet; Programm; Internationales Management; Wirtschaftssprache; Textproduktion; Computerunterstützte Übersetzung; Online-Recherche; Fremdsprache; Nachschlagewerk; Computerunterstütztes Lernen; E-Learning; Kauffrau; Kaufmann; Industriekauffrau; Betriebswirtschaftliches Studium